Micellization phenomena of biodegradable amphiphilic triblock copolymers consisting of poly(beta-hydroxyalkanoic acid) and poly(ethylene oxide) - Li, Jun (Langmuir : the ACS journal of surfaces and colloids, 2005)
This paper reports the studies on micelle formation of new biodegradable amphiphilic poly(ethylene oxide)-poly[(R)-3-hydroxybutyrate]-poly(ethylene oxide) (PEO-PHB-PEO) triblock copolymer with various PHB and PEO block lengths in aqueous solution. Transmission electron microscopy showed that the micelles took an approximately spherical shape with the surrounding diffuse outer shell formed by hydrophilic PEO blocks. The size distribution of the micelles formed by one triblock copolymer was demonstrated by dynamic light scattering technique. The critical micellization phenomena of the copolymers were extensively studied using the pyrene fluorescence dye absorption technique, and the (0,0) band changes of pyrene excitation spectra were used as a probe for the studies. For the copolymers studied in this report, the critical micelle concentrations ranged from 1.3 x 10(-5) to 1.1 x 10(-3) g/mL. For the same PEO block length of 5000, the critical micelle concentrations decreased with an increase in PHB block length, and the change was more significant in the short PHB range. It was found that the micelle formation of the biodegradable amphiphilic triblock copolymers consisting of poly(beta-hydroxyalkanoic acid) and PEO was relatively temperature-insensitive, which is quite different from their counterparts consisting of poly(alpha-hydroxyalkanoic acid) and PEO